Avatrombopag as alternative therapy for severe aplastic anemia patients who are intolerant or unresponsive to eltrombopag - Zhang, Ting; Yu, Qingling; Chen, Xiaoyu; Yang, Hui; Gong, Yuemin; Zhang, Yawen; Liu, Xiaoqing; Yang, Zhinan; Fang, Yu; Yan, Xue; Zhou, Xuan; Shi, Jinning; et al. (Frontiers in Immunology, 2024)
Eltrombopag (EPAG), a thrombopoietin receptor agonist, was approved for the treatment of severe aplastic anemia (SAA) combined with immunosuppressive therapy (IST). However, EPAG contains a typical biphenyl structure, which causes liver function damage. Twenty patients with SAA who 2 were intolerant or refractory to EPAG were enrolled in a multicenter prospective registry of the Chinese Eastern Collaboration Group of Anemia (ChiCTR2100045895) from October 2020 to June 2023: eight patients who were ineffective to EPAG, six with kidney impairment, and nine with abnormal liver function (two with concomitant liver and kidney impairment) were converted to AVA therapy with the median duration of AVA treatment was 6 (3-24) months. 17 cases (85%) achieved trilineage hematological response (HR): complete remission (CR) in 3 cases (15%), good partial remission (GPR) in 4 cases (20%), partial remission (PR) in 10 cases (50%), and no response (NR) in 3 cases (15%). The median time to response was 1.7 (0.5-6.9) months, with 16 cases (94%) achieving response within six months and 17 cases (100%) within 12 months. 9 cases (50%) achieved transfusion independence. AVA converted treatment was associated with higher neutrophil counts (0.8×10 9 /L vs 2.2×10 9 /L, p=0.0003), platelet counts (11×10 9 /L vs 39×10 9 /L, p=0.0008), hemoglobin count (59g/L vs 98g/L, p=0.0002), red cell count (1.06×10 12 /L vs 2.97×10 12 /L, p=0.001), and absolute reticulocyte count (31.99 ×10 9 /L vs 67.05×10 9 /L p=0.0004) were all significantly elevated compared with the pre-treatment level. After the conversion to AVA therapy, liver and kidney function indexes were maintained within the normal range, no AVA related grade 2 or higher adverse events occurred, and no thrombotic events occurred.The conversion to AVA was an optimal choice for patients with SAA who were EPAG intolerant or refractory.